The radiobiological principles of boron neutron capture therapy: A critical review - Hopewell, J. W. (2011)
The radiobiology of the dose components in a BNCT exposure is examined. The effect of exposure time in determining the biological effectiveness of γ-rays, due to the repair of sublethal damage, has been largely overlooked in the application of BNCT. Recoil protons from fast neutrons vary in their relative biological effectiveness (RBE) as a function of energy and tissue endpoint. Thus the energy spectrum of a beam will influence the RBE of this dose component. Protons from the neutron capture reaction in nitrogen have not been studied but in practice protons from nitrogen capture have been combined with the recoil proton contribution into a total proton dose. The relative biological effectiveness of the products of the neutron capture reaction in boron is derived from two factors, the RBE of the short range particles and the bio-distribution of boron, referred to collectively as the compound biological effectiveness factor. Caution is needed in the application of these factors for different normal tissues and tumors.